Rhus coriaria L. (Sumac) Demonstrates Oncostatic Activity in the Therapeutic and Preventive Model of Breast Carcinoma - Kubatka, Peter; Kello, Martin; Kajo, Karol; Samec, Marek; Liskova, Alena; Jasek, Karin; Koklesova, Lenka; Kuruc, Tomas; Adamkov, Marian; Smejkal, Karel; Svajdlenka, Emil; Solar, Peter; et al. (International journal of molecular sciences, 2020)
Comprehensive scientific data provide evidence that isolated phytochemicals or whole plant foods may beneficially modify carcinogenesis. The aim of this study was to evaluate the oncostatic activities of Rhus coriaria L. (sumac) using animal models (rat and mouse), and cell lines of breast carcinoma. R. coriaria (as a powder) was administered through the diet at two concentrations (low dose: 0.1% (w/w) and high dose: 1 % (w/w)) for the duration of the experiment in a syngeneic 4T1 mouse and chemically-induced rat mammary carcinoma models. After autopsy, histopathological and molecular analyses of tumor samples in rodents were performed. Moreover, in vitro analyses using MCF-7 and MDA-MB-231 cells were conducted. The dominant metabolites present in tested R. coriaria methanolic extract were glycosides of gallic acid (possible gallotannins). In the mouse model, R. coriaria at a higher dose (1%) significantly decreased tumor volume by 27% when compared to controls. In addition, treated tumors showed significant dose-dependent decrease in mitotic activity index by 36.5% and 51% in comparison with the control group. In the chemoprevention study using rats, R. coriaria at a higher dose significantly reduced the tumor incidence by 20% and in lower dose non-significantly reduced tumor frequency by 29% when compared to controls. Evaluations of the mechanism of oncostatic action using valid clinical markers demonstrated several positive alterations in rat tumor cells after the treatment with R. coriaria. In this regard, histopathological analysis of treated tumor specimens showed robust dose-dependent decrease in the ratio of high-/low-grade carcinomas by 66% and 73% compared to controls. In treated rat carcinomas, we found significant caspase-3, Bax, and Bax/Bcl-2 expression increases; on the other side, a significant down-regulation of Bcl-2, Ki67, CD24, ALDH1, and EpCam expressions and MDA levels. When compared to control specimens, evaluation of epigenetic alterations in rat tumor cells in vivo showed significant dose-dependent decrease in lysine methylation status of H3K4m3 and H3K9m3 and dose-dependent increase in lysine acetylation in H4K16ac levels (H4K20m3 was not changed) in treated groups. However, only in lower dose of sumac were significant decreases in the expression of oncogenic miR210 and increase of tumor-suppressive miR145 (miR21, miR22, and miR155 were not changed) observed. Finally, only in lower sumac dose, significant decreases in methylation status of three out of five gene promoters-ATM, PTEN, and TIMP3 (PITX2 and RASSF1 promoters were not changed). In vitro evaluations using methanolic extract of R. coriaria showed significant anticancer efficacy in MCF-7 and MDA-MB-231 cells (using Resazurin, cell cycle, annexin V/PI, caspase-3/7, Bcl-2, PARP, and mitochondrial membrane potential analyses). In conclusion, sumac demonstrated significant oncostatic activities in rodent models of breast carcinoma that were validated by mechanistic studies in vivo and in vitro.
Keywords: regulace genové exprese u nádorů; Animals; nádory prsu; apoptóza; proliferace buněk; cancer stem cells; Female; apoptosis; MDA-MB-231 cells; breast cancer; ženské pohlaví; Apoptosis; sumac; Cell Cycle; Mice, Nude; rostlinné extrakty; Gene Expression Regulation, Neoplastic; fytogenní protinádorové látky; lidé; Mice; Breast Neoplasms; angiogenesis; nádorové buňky kultivované; Mice, Inbred BALB C; myši; epigenetics; Rats, Sprague-Dawley; Antineoplastic Agents, Phytogenic; buněčný cyklus; rat; xenogenní modely - testy protinádorové aktivity; Tumor Cells, Cultured; Rhus coriaria; nádorové biomarkery; potkani Sprague-Dawley; myši inbrední BALB C; mikro RNA; Cell Proliferation; Plant Extracts; Xenograft Model Antitumor Assays; Biomarkers, Tumor; MicroRNAs; MCF-7 cells; cell proliferation; mouse; zvířata; myši nahé; Rhus; Humans